Analisis Strategi Bersaing Dalam Pengembangan Bisnis pada Home Industri Eceng Gondok Wiwit Collection @Witrove_ Kecamatan Karang Pilang Kota Surabaya - Virara Aprilia Purwannia; Lia Nirawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Competitive advantage becomes the endurance of a business in a competitive market to understand the value that can be created for the products offered in order to increase the attractiveness of the business. The purpose of the study was to determine the competitive strategy applied in business development at the home industry of water hyacinth Wiwit Collection @witrove_ Karang Pilang District, Surabaya City in an effort to face business competition. The research population is the resource person of the Wiwit Collection with a sample of resource persons on the criteria established by purposive sampling technique, which means that it is based on the research objectives. The data analysis technique used a SWOT analysis with the questionnaire method. The results showed that internal factors had a total weighted average of 1.31 with a strength factor of 4.24 and a weakness factor of 2.93, while the total external factor weighted average of 0.96 with an opportunity factor of 4.13 and a threat factor of 3.17. Wiwit Collection is in quadrant I implementing an aggressive strategy through the SO strategy which shows that the strengths and opportunities are relatively superior compared to the weaknesses and threats. While the WO and WT strategies can be used as an alternative, especially in the online marketing aspect. Keywords: Competitive Strategy, Business Development, SWOT Analysis